Native plants for landscape gardening - Tripathi, P C (Indian Horticulture, 2019)
India is a centre of crop diversity — the homeland of 167 cultivated species and 320 wild relatives of crop plants. Several plant species are used in commercial cultivation. There are several species which have potential for cultivation in future. It is important to incorporate these plant species in landscaping. This helps in conserving the biological heritage and conservation of plant species. Many of wild edible species have attractive foliage and plant architecture. Apart from food values, these species can be utilized for beatification. The incorporation of native plants in landscape gardening interrelated with other elements of natural ecosystem, such as insects and soil organisms, and they contribute subtle functions that are important for overall health of the ecosystem.